Pengaruh Auditor Switching, Financial Distress, Dan Laba Perusahaan Terhadap Audit Report Lag: (Studi Empiris pada Perusahaan Keuangan yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2017-2021) - Syfa Fauziah (Jurnal Literasi Akuntansi, 2023)
This study aims to determine the effect of auditor switching, Financial Distress, and company profits simultaneously on Audit Report Lag and the partial effect of auditor switching, Financial Distress, and company profits on Audit Report Lag . This type of research is quantitative in nature, and the data used is secondary data with the media in the form of financial company financial reports taken from IDX. The population used in this study are financial companies listed on the Indonesia Stock Exchange during the 2017-2021 period. Data management uses eviews 9. Based on the results of the tests conducted, it can be seen that auditor switching, Financial Distress, and company profits simultaneously have an influence on Audit Report Lag with a probability value (F-Statistic) of 0.010215 <0.05. Auditor switching has no effect on Audit Report Lag with a probability value of 0.5297 > 0.05, Financial Distress has no effect on Audit Report Lag with a probability value of 0.6731 > 0.05, corporate profits affect Audit Report Lag with a probability value of 0.0009 < 0.05. Keywords: Auditor Switching; Financial Distress; and Company Profits